How do project management competencies change within the project management career model in large Chinese construction companies?. Issue 3 (April 2019) - Chen, Tao; Fu, Meiqing; Liu, Rui; Xu, Xuanhua; Zhou, Shenbei; Liu, Bingsheng
Abstract: Due to the increasing complexity and flexibility of business activities, project-based organizations have become common. In such organizations, project management competencies, which refer to a collection of knowledge, personal attitudes, skills, and relevant experience, are core assets that must be taken seriously. Formalized project management career paths have been widely implemented in the construction industry. However, most recent studies treat project management competencies as static constructs and fail to consider their dynamic changes as a career path advances. To fill this gap in the literature, this study conducted an empirical examination of project management competencies integrated with a career model for the construction industry. First, key project management competencies are identified through a literature review. Then, a project management career model for large Chinese construction companies is developed based on an empirical investigation of six large Chinese construction companies from various sectors. Moreover, a quantitative analysis is performed to explore how these competencies dynamically change as position levels rise in the career model. The research findings indicate that significant differences in project management competencies exist at different levels of the career model. However, the distribution remains steady at different project management position levels for conceptual and organizational competencies, human competencies, and technical competencies. Highlights: A project management career model for Chinese large contractors is developed. The change of project management competency in proposed career model is analyzed. The importance of project management competency increases first, then decrease. Project management competency reaches the peak at project manager level. Human skills are the most important at all project management position levels.